Réponses

2014-01-20T19:36:15+01:00
2x/(x³ + 1) 
x³ + 1 = (x+1)(x² + x + 1)
2x/(x³+1) = A/(x+1) + (Bx+D)/(x²+x+1) = [A(x²+x+1) +(Bx+D) (x+1) ](x+1)(x²+x+1)
et 2x = Ax² + Ax + A + Bx² + Dx + Bx + D 
2x = (A+B)x² + (A+B+D)x + A+D 
A+B = 0
A+B+D = 2
A+D = 0
A = -B => D = 2 donc A = -2 et B = 2 
on a alors à intégrer 
-2/x+1 + (2x +2)/(x²+x+1)

-2/x+1 => -2ln(x+1)
et( 2x + 1 + 1 )/(x² + x + 1) = (2x+1)/ x² + x + 1) + 1/(x² + x + 1 
(2x+1)/ x² + x + 1) => ln(x² + x + 1) 
pour le 1/(x²+x+1) je ne sais pas